miR-124 Modulates Gefitinib Resistance through SNAI2 and STAT3 in Non-small Cell Lung Cancer - 胡发涌 曹小年 徐沁孜 邓豫 来森艳 马静 胡俊波 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
Gefitinib is used as a first-line treatment for advanced non-small cell lung cancer（NSCLC）.Unfortunately,most NSCLC patients inevitably develop gefitinib resistance during treatment.In addition to EGFR mutation status,the mechanisms involved are largely unknown.In this study,we showed that mi R-124,a tumor suppressor,was significantly down-regulated in gefitinib-resistant NSCLC patients and cell lines compared with gefitinib-sensitive patients and cell lines.In addition,the mi R-124 depletion induced gefitinib resistance,and mi R-124 overexpression sensitized gefitinib-resistant cells to gefitinib.Mechanistic analysis revealed that mi R-124 decreased SNAI2 and STAT3 expression by directly targeting their 3＇UTRs and that knocking down SNAI2 or STAT3 partly reversed the gefitinib resistance induced by mi R-124 depletion.Our data demonstrate that the mi R-124 plays a new critical role in acquired resistance to gefitinib and that the manipulation of mi R-124 might provide a therapeutic strategy for reversing acquired gefitinib resistance.